Educación híbrida y su influencia en el rendimiento académico de los estudiantes de la Unidad Educativa Eugenio Espejo de la Parroquia Clemente Baquerizo durante el periodo 2024 - 2025 - Aviles Amador, Ginger Milena (2025)
The objective of this project is to determine how hybrid education influences students' academic performance, as well as to identify whether this modality is perceived positively, negatively, or neutrally in relation to academic results. The COVID-19 pandemic gave rise to hybrid education, a new learning modality that presents challenges, such as lack of internet connectivity and limited access to digital devices. Likewise, teachers had to adapt quickly, developing new teaching strategies and training in the use of educational platforms. Blended research allows us to identify how hybrid education has had a positive influence on students' learning and academic performance, facilitating their autonomous education through access to various educational platforms. However, some students continue to face difficulties related to connectivity and access to electronic devices. This research also recognizes benefits and challenges of the hybrid modality, offering strategies used to improve academic performance. Furthermore, by addressing the challenges of connectivity and access to technology, the research contributes to a broader debate on equity in education, analyzing the accessibility of this modality for all students and suggesting improvements in technological infrastructure to ensure equal opportunities in learning. In addition, it highlights the importance of maintaining a balance between face-to-face classes and online activities, to make the most of the advantages that each modality offers, always with the purpose of improving the educational experience and academic results.